Management experience of care workers during epidemic prevention and control of COVID-19 - Na Cheng; Run-Xi Tian; Nan Tong; Qing Gong; Jia-Yue Li; Bao-Jing Wu; De-Yu Kong (Wolters Kluwer Medknow Publications, 2020)
Since the rapid spread of COVID-19, our hospital has actively implemented the idea of "preventing the coronavirus from entering." We paid close attention to details, rapidly carried out personnel and material management at all levels, and strived to do a good job in the prevention and control of the epidemic, so as to achieve zero infection. Patients' carers are an important part of quality care. Lacking of protection knowledge of infectious diseases would increase the risk of nosocomial infection. Therefore, our nursing department set up a team of epidemic prevention and control management. The team made the revision on contingency plans and care management regulations during the outbreak of COVID-19, strengthened epidemic prevention and control knowledge training, carried out the supervision inspection work, and paid attention to humanized management measures to provide an important guarantee for victory over the COVID-19.